Approach to a Child with Cow’s Milk Allergy (Bangladesh Journal of Child Health, 2024)
Cow’s milk allergy is a common problem in childhood that needs frequent visits to a pediatrician. The objective of this review is to provide the general pediatrician with an overview of cow’s milk allergy in children discussing the etiology, patient evaluation, and management. This review provides an approach to a child with cow’s milk allergy based on the best available evidence from electronic literature searches. Cow’s milk allergy may be IgE-mediated, non-IgE-mediated, and mixed. IgE-mediated reactions occur immediately after ingestion of milk. Skin manifestations like erythema, hives, pruritus, angioedema, and flaring of eczematous lesions are common manifestations of IgEmediated food allergy. Non-IgE-mediated cow’s milk allergies are proctocolitis, enterocolitis, enteropathy, and contact dermatitis. Cow’s milk-induced allergic proctocolitis is the common cause of rectal bleeding from 1 day to 6 months of age. The key to the diagnosis of food allergy depends on obtaining a good history and physical examination. Quantitative measurements of serum cow’s milk specific IgE and skin prick test are useful tests. Strict avoidance of the offending food is the mainstay of management.Bangladesh J Child Health 2023; Vol 47 (2) : 59-64